Aves rapaces diurnas en bosques aluviales inundables de mohena caño en la época de vaciante, Loreto - Perú - López Sifuentes, Jean Pier (2022)
Since august to october 2020 we perform observations of daytime raptors in no flooded epoc in Mohenacaño zone, by lineal transect and boat census. The composition of daytime raptors it was conformated for the órders Accipitriformes and Falconiformes with 3 families (Pandionidae, Accipitridae and Falconidae) and 13 species; with 2 species boreal migrants Pandion haliaetus and Falco peregrinus, and intratropical migrant Caracara plancus, and others species was residents with wide distribution in the peruvian Amazonia. Only 3 species reports densities more higher: Milvago chimachima 31.11 ind/km2, Rupornis magnirostris 6.67 ind/km2 and Rostrhamus sociabilis 5.00 ind/km2 and others they reported densities les a one individual. We conclude that the composition of the daytime raptors distributed in de Mohenacaño zone in not flooded epoc, was confomated by Accipitriformes and Falconiformes, with a richness of 13 species.